2013
DOI: 10.1097/mcd.0b013e32835b9017
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the clinical spectrum of two adolescent male patients with Alström syndrome

Abstract: Alström syndrome is a rare disorder typified by early childhood obesity, neurosensory deficits, cardiomyopathy, progressive renal and hepatic dysfunction, and endocrinological features such as severe insulin resistance, type 2 diabetes, hyperlipidemia, and hypogonadism. Widespread fibrosis leads to multiple organ failure. Mutations in ALMS1 cause Alström’s syndrome. Two age-matched, unrelated adolescent males of Serbian descent with Alström syndrome underwent an extensive workup of blood chemistries, and ophth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Kuburović et al ( 2013) [8] reported on a patient with an unusual clinical presentation and a heterozygous ALMS1 pathogenic variant in exon 16, c.10568_10569delAT; p.His-3523Terfs17. The clinical features included centripetal obesity with selective loss of adipose tissue in his legs and gluteal region, acanthosis nigricans, gynecomastia, scoliosis, glomerulopathy, subclinical primary hypogonadism, restrictive filling of the left ventricle, and significant early atrial contraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kuburović et al ( 2013) [8] reported on a patient with an unusual clinical presentation and a heterozygous ALMS1 pathogenic variant in exon 16, c.10568_10569delAT; p.His-3523Terfs17. The clinical features included centripetal obesity with selective loss of adipose tissue in his legs and gluteal region, acanthosis nigricans, gynecomastia, scoliosis, glomerulopathy, subclinical primary hypogonadism, restrictive filling of the left ventricle, and significant early atrial contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Their second patient had epilepsy at the age of two years, followed by vision and hearing impairments, hypertension, hepatic dysfunction, mental retardation (IQ 40), hypogonadotropic hypogonadism, renal dysfunction, acanthosis nigricans, and truncal obesity with reduced femoral-gluteal fat. The authors propose that variable neurological involvement, including seizure activity, should be included as a rare occurrence, and as a part of the phenotypic spectrum of ALMS [8].…”
Section: Discussionmentioning
confidence: 99%
“…In adolescence the testes and penis are small, and the onset of puberty is sometimes delayed. Secondary sexual characteristics are usually normal [142]. The occurrence of normal to high FSH and LH and low testosterone levels suggests primary hypogonadism.…”
Section: Diseases Associated With Defects Of Hormone Biosynthesis or mentioning
confidence: 99%
“…AS patients also present short stature, hypogonadotropic hypogonadism in affected males, and polycystic ovarian syndrome (PCOS) in affected females. In AS patients, clinical features may appear at different times throughout childhood followed by progressive multiorgan failure which reduces life expectancy where patients rarely live beyond their 5th decade of life ( 2 ). Although clinical assessment is considered as the first line of diagnosis, gradual multiorgan dysfunction and variable expressivity of the disease within the same family members make it more challenging ( 3 ).…”
Section: Introductionmentioning
confidence: 99%